2011
DOI: 10.4315/0362-028x.jfp-10-405
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam Inactivation of a Norovirus Surrogate in Fresh Produce and Model Systems

Abstract: Norovirus remains the leading cause of foodborne illness, but there is no effective intervention to eliminate viral contaminants in fresh produce. Murine norovirus 1 (MNV-1) was inoculated in either 100 ml of liquid or 100 g of food. The inactivation of MNV-1 by electron-beam (e-beam), or high-energy electrons, at varying doses was measured in model systems (phosphate-buffered saline [PBS], Dulbecco's modified Eagle's medium [DMEM]) or from fresh foods (shredded cabbage, diced strawberries). E-beam was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…There is a linear relationship between dose and level of virus inactivation. This linear relationship between virus inactivation and ionizing radiation has been reported earlier (2,26,35). Poliovirus exhibited greater resistance to E-beam irradiation than did rotavirus (Table 1).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…There is a linear relationship between dose and level of virus inactivation. This linear relationship between virus inactivation and ionizing radiation has been reported earlier (2,26,35). Poliovirus exhibited greater resistance to E-beam irradiation than did rotavirus (Table 1).…”
Section: Discussionsupporting
confidence: 52%
“…There were, however, no statistically significant differences between the D 10 values of either virus on spinach and the D 10 values of that virus on lettuce. There are other reports in the literature which suggest that the matrix in which the organisms are present influences the reduction kinetics (1,2,22,35,39). Researchers have recently reported that the human norovirus surrogate, murine norovirus, showed differential reduction when exposed to E-beam irradiation depending on whether the virus was present on cabbage or strawberries (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of the enteric viruses within the oyster's tissue could have an influence on their sensitivity to ionizing radiation if it is protected from the reactive oxygen species. It has been reported that MNV shows differential inactivation depending on whether it is present on cabbage or strawberries (32). However, using poliovirus and rotavirus, we have recently shown that while there are inactivation differences on fresh produce, such as lettuce and spinach, these observed differences were not statistically significant (23).…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have been done with irradiation and UV radiation for inactivation of viruses; results indicate that their utility is limited (77,201,212). Although these interventions cannot completely eliminate the risk of norovirus, infection risks may be reduced.…”
Section: Recommendationsmentioning
confidence: 95%